2023
DOI: 10.1371/journal.pone.0281845
|View full text |Cite
|
Sign up to set email alerts
|

IL-17A regulates autophagy and promotes osteoclast differentiation through the ERK/mTOR/Beclin1 pathway

Abstract: Bone is a frequent target of tumor metastasis, with high incidence rate and poor prognosis. Osteoclasts play a key role in the process of tumor bone metastasis. Interleukin-17A (IL-17A) is an inflammatory cytokine, highly expressed in a variety of tumor cells, that can alter the autophagic activity of other cells, thereby causing corresponding lesions. Previous studies have shown that low concentration IL-17A can promote osteoclastogenesis. The aim of this study was to clarify the mechanism of low concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…128 A low concentration of IL-17A can inhibit the phosphorylation of ERK and mTOR, increase the expression of Beclin1, lead to the increase of autophagy of osteoclast precursors, reduce the apoptosis of osteoclast precursors, and promote osteoclast differentiation. 134 In addition, a low concentration of IL-17A can also promote the autophagy of osteoclast precursors by activating the RANKL-JNK pathway. 135 However, the effect of high concentrations on osteoclasts and osteoclast precursors is controversial.…”
Section: Il Familymentioning
confidence: 99%
See 1 more Smart Citation
“…128 A low concentration of IL-17A can inhibit the phosphorylation of ERK and mTOR, increase the expression of Beclin1, lead to the increase of autophagy of osteoclast precursors, reduce the apoptosis of osteoclast precursors, and promote osteoclast differentiation. 134 In addition, a low concentration of IL-17A can also promote the autophagy of osteoclast precursors by activating the RANKL-JNK pathway. 135 However, the effect of high concentrations on osteoclasts and osteoclast precursors is controversial.…”
Section: Il Familymentioning
confidence: 99%
“…A low concentration of IL‐17A can promote the differentiation of osteoclast precursors 133 and inhibit the apoptosis of osteoclast precursors derived from raw264.7 128 . A low concentration of IL‐17A can inhibit the phosphorylation of ERK and mTOR, increase the expression of Beclin1, lead to the increase of autophagy of osteoclast precursors, reduce the apoptosis of osteoclast precursors, and promote osteoclast differentiation 134 . In addition, a low concentration of IL‐17A can also promote the autophagy of osteoclast precursors by activating the RANKL‐JNK pathway 135 .…”
Section: Cytokines Of Immunology Play a Crucial Role In Osteoimmunolo...mentioning
confidence: 99%
“…The target sequences were as follows: 5 0 -CCTAAGGTTAAGTCGCCCTCG-3 0 (snc) and 5 0 -CCCAAATTCTGAGGACAAGAA-3 0 (si). siRNAs were transfected into A549 cells using Lipofectamine 3000 reagent (Thermo Fisher Scientific, Waltham, MA, USA), following the manufacturer's instructions [11].…”
Section: Rna Interferencementioning
confidence: 99%
“…In addition, many studies showed that IL-17A affects bone remodeling [9,10]. Exogenous IL-17A affects autophagy in osteoclast precursors (OCPs), thus affecting osteoclast differentiation [11]. Apoptosis refers to programmed cell death that occurs during development or under the influence of specific factors [12].…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin-17A (IL-17A) can promote the differentiation of OCs precursors into OCs, inhibit the phosphorylation of extracellular regulated kinase (ERK) to increase the expression of Beclin-1, enhance the autophagy activity of OCs precursors through the ERK/mTOR/Beclin1 pathway, and promote OCs differentiation. 107 Chung et al found that knockout of Beclin-1 inhibited RANKL-mediated activation of JNK and p38, thereby inhibiting the expression of OCs-specific gene NFATc1. 108 In vitro, autophagy is activated during RANKL-induced OCs differentiation and requires TRAF6-mediated Beclin-1 ubiquitination, and Beclin-1 knockout mice exhibit impaired OCs bone resorption and thickened bone cortex.…”
Section: Signaling Pathways Involved In Autophagy In Obs and Ocsmentioning
confidence: 99%